Effects of Separate and Combined Exposure of Cadmium and Lead on the Endochondral Ossification in Bufo gargarizans. (8th April 2022) - Chen, Aixia; Deng, Hongzhang; Song, Xiuling; Liu, Xiaoli; Chai, Lihong
Abstract: Cadmium (Cd) and lead (Pb) are ubiquitous in aquatic environments and most studies have examined the potential effects of Cd or Pb alone on aquatic organisms. In the present study, chronic effects of Cd and Pb, alone and in combination, on Bufo gargarizans were investigated by exposing embryos to these contaminants throughout metamorphosis. Significant reductions in body mass and snout‐to‐vent length were observed in B. gargarizans at Gosner stage 42 (Gs 42) and Gs 46 exposed to a Cd/Pb mixture. Single and combined exposure with Cd and Pb induced histological alterations of the thyroid gland characterized by reduced colloid area and thickness of epithelial cells. There was a significant decrease in the maximum jump distance of froglets exposed to Cd alone and the Cd/Pb mixture, and the jumping capacity showed a positive correlation with hind limb length and tibia/fibula. Moreover, single metals and their mixture induced reduction of endochondral bone formation in B. gargarizans . Transcriptomic and real‐time quantitative polymerase chain reaction results showed that genes involved in skeletal ossification ( TRα, TRβ, Dio2, Dio3, MMP9, MMP13, Runx1, Runx2, and Runx3 ) were transcriptionally dysregulated by Cd and Pb exposure alone or in combination. Our results suggested that despite the low concentration tested, the Cd/Pb mixture induced more severe impacts on B. gargarizans . In addition, the Cd/Pb mixture might reduce chances of survival for B. gargarizans froglets by decreasing size at metamorphosis, impaired skeletal ossification, and reduction in jumping ability, which might result from dysregulation of genes involved in thyroid hormone action and endochondral ossification. The findings obtained could add a new dimension to understanding of the mechanisms underpinning skeletal ossification response to heavy metals in amphibians. Environ Toxicol Chem 2022;41:1228–1245. © 2022 SETAC